The Health-Oriented Transportation Model: Estimating the health benefits of active transportation. (September 2021) - Younkin, Samuel G.; Fremont, Henry C.; Patz, Jonathan A.
Abstract: Introduction: Overdependence on gasoline-powered personal automobiles in industrialized urban settings has resulted in transportation behaviour that is detrimental to public health. Risk not only stems from an increase in air pollution, but also, and more significantly for wealthy nations, from a reduction in physical activity. Tools and models that demonstrate the magnitude of the health benefits of physical activity are needed to inform policies addressing the epidemic of physical inactivity and to help promote environmentally sustainable cities. Methods: The Health-Oriented Transportation (HOT) model is a transparent and easily accessible tool that allows users to assess the current and potential health benefits of active transportation (walking or cycling) using data from a one-day travel survey. As a case-study, we apply the HOT model to the population of London, England, using the London Travel Demand Survey. Results: We estimate that in the 2016 adult population of London, 1, 618 and 2, 720 deaths were averted in the inner and outer boroughs, respectively, due to transportation-related physical activity; an additional 364 and 946 deaths are potentially averted if the proportion of the adult population that walked or cycled at least weekly from 80% and 73% to 100% in the inner and outer boroughs, respectively. A 50% increase in walking/cycling mode share among active travellers would result in a 2.5% reduction in premature deaths in the adult population of London. Conclusions: Estimating the potentially large health benefits arising from active transportation in an urban setting can provide key public health information for urban planners and local officials, informing investments in infrastructure and critical public health programs. Highlights: Thousands of deaths per year are averted in London, England due to walking and cycling. If all London adults walked or cycled, hundreds of deaths per year could be averted. A 50% increase in walking/cycling mode share among active travelers could reduce London's adult mortality rate by 2.5%.